2018
DOI: 10.1080/03069885.2018.1472368
|View full text |Cite
|
Sign up to set email alerts
|

Yoga as an adjunct to trauma-focused counselling for survivors of sexual violence: a qualitative study

Abstract: Although evidence exists for the therapeutic effectiveness of yoga for people with a range of mental health difficulties, further research is necessary to determine its contribution to recovery from sexual violence. This study used Interpretative Phenomenological Analysis to explore the experience of a group-based Forrest yoga programme for woman recovering from experiences of sexual violence. The main themes to emerge were: the importance of being in a group; yoga as a means of facilitating personal learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…Female participants in a study of a 10-week TSY group reported experiencing increased sense of control and confidence as well as “gratitude and compassion, relatedness, acceptance, centeredness, and empowerment” (West et al, 2017, p. 173). Other studies that focused on sexual assault survivors found similar themes such as increased tolerance for being aware in the present moment, ability to use breath to feel more stable, reduced anxiety and negative self-talk, enhanced acceptance and understanding of self (Stevens & McLeod, 2019), enhanced body awareness, regulation, and body and mind connection (Silverberg, 2019; Stevens & McLeod, 2019). Although much of the qualitative research focuses on the general population of survivors of sexual violence and their experiences in TSY groups, a few studies examine TSY as a tool for healing posttraumatic stress among military veterans.…”
Section: Participants’ Lived Experiences In Tsy Interventionsmentioning
confidence: 87%
See 4 more Smart Citations
“…Female participants in a study of a 10-week TSY group reported experiencing increased sense of control and confidence as well as “gratitude and compassion, relatedness, acceptance, centeredness, and empowerment” (West et al, 2017, p. 173). Other studies that focused on sexual assault survivors found similar themes such as increased tolerance for being aware in the present moment, ability to use breath to feel more stable, reduced anxiety and negative self-talk, enhanced acceptance and understanding of self (Stevens & McLeod, 2019), enhanced body awareness, regulation, and body and mind connection (Silverberg, 2019; Stevens & McLeod, 2019). Although much of the qualitative research focuses on the general population of survivors of sexual violence and their experiences in TSY groups, a few studies examine TSY as a tool for healing posttraumatic stress among military veterans.…”
Section: Participants’ Lived Experiences In Tsy Interventionsmentioning
confidence: 87%
“…While our study was unique in that it specifically examined the stress experiences of participants before and after each session of the BIB group across 8 weeks, many of the themes that emerged from our study aligned with the thematic results of other studies examined in our literature review. The most common experience reported by participants in TSY interventions, which was seen across studies we reviewed, was an improved connection to, awareness of, and relationship with one’s body and mind (Bluntzer, 2016; Cushing et al, 2018; Gulden & Jennings, 2016; Jindani & Khalsa, 2015; Neukirch et al, 2019; Rhodes, 2015; Schintler et al, 2020; Silverberg, 2019; Stevens & McLeod, 2019). For example, Cushing and colleagues (2018) reported a theme they referred to as, sense of calm and peace allowing for enhanced body awareness, whereas Stevens and McLeod (2019) referred to a theme of enhanced acceptance and understanding of self, a theme they referred to as the ability to use breath to feel more stable, reduced anxiety and negative self-talk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations